2017
DOI: 10.1111/caim.12223
|View full text |Cite
|
Sign up to set email alerts
|

Managing for variability: A neuroscientific approach for developing strategic agility in organizations

Abstract: The neuroscientific literature reveals that the brain changes over time, and the type of change (plasticity) that results is not random. While the brain exhibits certain evolutionary prejudices, individual plasticity and the kind of thinking enabled can be shaped by, and can shape, organizational priorities and operations. Organizational focus on structure and procedural efficiency is shown to foster fixed thinking, while cultivation of “practiced varying” skills encourages thinking agility. Agile thinking is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…For organizations for whom rapid production of knowledge and innovation is crucial for survival in complex competitive landscapes (Koch & Leitner, 2008;Uhl-Bien et al, 2007), such as Swedish music streaming firm Spotify, a key management challenge is learning what to structure and what not to structure (Hill, Cromartie, & McGinnis, 2017;McKelvey, 1999;Vidgen & Wang, 2009) or how to strike a balance between order and disorder, often referred to as "the edge of chaos" (Lewin, Long, & Carroll, 1999;McDaniel & Walls, 1997). The edge of chaos provides organizations with both sufficient "stimulation and freedom to experiment and adapt but also with sufficient frameworks and structure to ensure they avoid complete disorderly disintegration" (McMillan, 2004, p. 22).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For organizations for whom rapid production of knowledge and innovation is crucial for survival in complex competitive landscapes (Koch & Leitner, 2008;Uhl-Bien et al, 2007), such as Swedish music streaming firm Spotify, a key management challenge is learning what to structure and what not to structure (Hill, Cromartie, & McGinnis, 2017;McKelvey, 1999;Vidgen & Wang, 2009) or how to strike a balance between order and disorder, often referred to as "the edge of chaos" (Lewin, Long, & Carroll, 1999;McDaniel & Walls, 1997). The edge of chaos provides organizations with both sufficient "stimulation and freedom to experiment and adapt but also with sufficient frameworks and structure to ensure they avoid complete disorderly disintegration" (McMillan, 2004, p. 22).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Thus, the characteristics of leadership are an important predictor of organizational survival or success. If the leaders have an agile thinking, as we have noticed in other section, then they can view all kind of problems from different perspectives and they can more easily cope with them, using different and innovative approaches and fostering organizational plasticity and agility (Hill et al, 2017). Leaders must drive communication, motivation and collaboration among employees, promoting actively their flexibility, agility and adaptability to handle with a changing and unpredictable business environment (Keister, 2014).…”
Section: Leadershipmentioning
confidence: 98%
“…Behavioural plasticity is defined by the extent to which a person is affected by external factors (Pierce, Gardner, Dunham, & Cummings, 1993) and has been studied by several scholars (e.g., Eden & Kinnar, 1991;Elengovan & Xie, 1999). More, neuroscience research has been showing that the brain changes over time, what is called brain plasticity, and this can influence organizational priorities and operations (Hill, Cromartie, & McGinnis, 2017). These authors showed the linkage between agile thinking (Garlick, 2002) and the organizational plasticity development that leads to enhancement of organizational agility.…”
Section: Organizational Plasticitymentioning
confidence: 99%
See 2 more Smart Citations